Survey on Handwritten Signature Biometric Data Analysis for Assessment of Neurological Disorder using Machine Learning Techniques. Issue 2 (2022) - Gornale, Shivanand S.; Kumar, Sathish; Siddalingappa, Rashmi; Hiremath, Prakash S.
No abstract available